PENGARUH KECERDASAN KOGNITIF DENGAN SELF CONTROL SISWA SMP KOTA JAMBI - Nadiyah, Rifka; Herlambang, Suparjo (Jurnal Kopendik, 2022)
The impact of Body Shame on learning concentration caused is indicated by the behavior of AZ often experiencing delays in collecting assignments, and often arriving late to school. AZ feels lazy to come to school if he has to meet his friend who often compares his physique. From these various things, AZ often experiences a decrease in learning concentration. The impact of Body Shame is seen from the level of depression. This impact is illustrated in the perspective of AZ's subject who is often inferior, embarrassed, over the condition of his physical body that is not comparable or not beautiful compared to other friends. Due to the assessment of the views of his classmates who often mock AZ's small and petite physique and has a slightly dark skin color, AZ always instills in him the comparison of himself to other friends. This view produces repeated shame and anxiety in AZ. The emotional experience that is formed is what causes Depression to affect AZ for the Body Shame act by his friends. seen based on the loss of self-confidence, the visible impact is that AZ prefers to be alone, closed and refuses to socialize with friends so that AZ feels inferior to other friends' observations about AZ's physicality, feels ashamed to join other friends and withdraws from the social environment.